1998
DOI: 10.1103/physreve.58.4758
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of vibration-induced compaction of powders

Abstract: We propose a theory which describes the density relaxation of loosely packed, cohesionless granular material under mechanical tapping. Using the compactivity concept we develop a formalism of statistical mechanics which allows us to calculate the density of a powder as a function of time and compactivity. A simple fluctuation-dissipation relation which relates compactivity to the amplitude and frequency of a tapping is proposed. Experimental data of E.R.Nowak et al. [Powder Technology 94, 79 (1997) ] show how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 8 publications
3
61
1
Order By: Relevance
“…Due to the clustering long-term temperature evolution is T ∼ t −2/3 which is different from Haff's law T ∼ t −2 derived for the spatially-homogeneous cooling. Efrati et al (2005) argue that flow by inertia represents a generic intermediate asymptotic of unstable free cooling of dilute granular gases consistent with the Burgers equation (19) description of one-dimensional gas of "sticky particles" suggested by Nie et al (2002).…”
Section: A Clustering In Freely Cooling Gasesmentioning
confidence: 86%
See 2 more Smart Citations
“…Due to the clustering long-term temperature evolution is T ∼ t −2/3 which is different from Haff's law T ∼ t −2 derived for the spatially-homogeneous cooling. Efrati et al (2005) argue that flow by inertia represents a generic intermediate asymptotic of unstable free cooling of dilute granular gases consistent with the Burgers equation (19) description of one-dimensional gas of "sticky particles" suggested by Nie et al (2002).…”
Section: A Clustering In Freely Cooling Gasesmentioning
confidence: 86%
“…Meerson and Puglisi (2005) conducted molecular dynamics simulations of the clustering instability of a freely cooling dilute inelastic gas in a quasi-one-dimensional setting. This problem was also examined in the framework of granular hydrodynamics by Efrati et al (2005). It was observed that, as the gas cools, stresses become negligibly small, and the gas flows only by inertia.…”
Section: A Clustering In Freely Cooling Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the above is true, the compactivity will be an increasing function of the vibration intensity, because the density over the "reversible" curve decreases with the tapping strength. In fact, this kind of behavior has been found in a simple model of a granular system described in terms of a Fokker-Planck equation [6].…”
Section: Introductionmentioning
confidence: 98%
“…This is, for instance, the behavior found in the simple two-volume model considered in Ref. [6]. In general, this property must be checked once the relationship between Γ and X, X = f (Γ), has been derived for each specific model.…”
Section: Some General Dynamical Propertiesmentioning
confidence: 99%